Baicalin and baicalein in modulating tumor microenvironment for cancer treatment: A comprehensive review with future perspectives - Ruolei Wang; Chunyan Wang; Lianheng Lu; Fuwen Yuan; Feng He (Elsevier, 2024)
Cancer is a leading cause of death worldwide. The burden of cancer incidence and mortality is increasing rapidly. New approaches to cancer prevention and treatment are urgently needed. Natural products are reliable and powerful sources for anticancer drug discovery. Baicalin and baicalein, two major flavones isolated from Scutellaria baicalensis Georgi, a multi-purpose traditional medicinal plant in China, exhibit anticancer activities against multiple cancers. Of note, these phytochemicals exhibit extremely low toxicity to normal cells. Besides their cytotoxic and cytostatic activities toward diverse tumor cells, recent studies demonstrated that baicalin and baicalein modulate a variety of tumor stromal cells and extracellular matrix (ECM) in the tumor microenvironment (TME), which is essential for tumorigenesis, cancer progression and metastasis. In this review, we summarize the therapeutic potential and the mechanism of action of baicalin and baicalein in the regulation of tumor microenvironmental immune cells, endothelial cells, fibroblasts, and ECM that reshape the TME and cancer signaling, leading to inhibition of tumor angiogenesis, progression, and metastasis. In addition, we discuss the biotransformation pathways of baicalin and baicalein, related therapeutic challenges and the future research directions to improve their bioavailability and clinical anticancer applications. Recent advances of baicalin and baicalein warrant their continued study as important natural ways for cancer interception and therapy.